Global prevalence of persistent neuromuscular symptoms and the possible pathomechanisms in COVID-19 recovered individuals: A systematic review and meta-analysis - Jhonny K. Fajar; Muhammad Ilmawan; Sukamto Mamada; Endang Mutiawati; Milda Husnah; Hanifah Yusuf; Firzan Nainu; Salin Sirinam; Synat Keam; Youdiil Ophinni; Francesco Rosiello; Marhami Fahriani; Sandro GV. Rosa (Narra Sains Indonesia, 2021)
This study was conducted to determine the prevalence of prolonged neuromuscular symptoms, including fatigue, anosmia, headache, myalgia, and joint pain in COVID-19 survivors hospitalized with mild, moderate, or severe infections worldwide. The search was conducted up to January 30th, 2021 using three databases (PubMed, Scopus, and Web of Science) to identify potentially eligible studies. Data on study characteristics, follow-up characteristics, and severity of COVID-19 during hospitalization were collected in accordance with PRISMA guidelines. The Newcastle-Ottawa scale was used to assess the quality of relevant articles. The estimated prevalence of specific prolonged neuromuscular symptoms and the association between COVID-19 severity and occurrence of prolonged neuromuscular symptoms was analyzed wherever appropriate. Database search yielded 4,050 articles and 22 articles were included for meta-analysis. The estimated prevalence of prolonged fatigue was recorded in 21.2% (95%CI: 11.9%–34.8%) of 3,730 COVID-19 survivors. Persistent anosmia was recorded in 239 of 2,600 COVID-19 survivors (9.7%, 95%CI: 6.1%–15.2%). In 84 out of 2,412 COVID-19 survivors (8.9%, 95%CI: 3.2%–22.6%), prolonged headache was observed. A total of 53 out of 1,125 COVID-19 patients (5.6%, 95%CI: 2.1%–14.2%) complained of persistent myalgia even after being discharged from the hospital. The prevalence of prolonged joint pain was in 15.4% (95%CI: 8.2%–27.2%) of subjects. Due to data scarcity on COVID-19 severity and prolonged neuromuscular symptoms, association analysis could not be conducted. Widespread concern regarding long-term impacts of COVID-19 was raised after several studies reported prolonged symptoms in COVID-19 survivors. Numerous theories have been proposed to address this concern; however, as the research on this pandemic is still ongoing, no explanation is definitive yet. Therefore, follow-up studies in COVID-19 survivors after recovery from COVID-19 are warranted to determine the pathogenesis of prolonged symptoms. PROSPERO registration: CRD42021242332.